SMART SRINAGAR AND BEYOND: URBAN TRANSFORMATION AS A CATALYST FOR RURAL DEVELOPMENT IN THE KASHMIR VALLEY - Asif Bashir; Rico Nur Ilham (RADJA PUBLIKA, 2025)
The metamorphosis of Srinagar into a Smart City represents a paradigmatic shift in the developmental discourse of the Kashmir Valley, wherein the urban sphere is increasingly envisaged as a catalyst for broader regional transformation. Conventionally, smart city initiatives have been critiqued for their technocentric orientation and metropolitan exclusivity; however, in a fragile, conflict-prone, and ecologically sensitive milieu such as Kashmir, the implications transcend the municipal boundary. This paper interrogates the urban–rural dialectic by situating Srinagar’s smart city trajectory within the wider developmental ecology of the Valley, emphasizing the multifarious intersections through which urban renewal reconfigures rural economies, governance modalities, service delivery architectures, and livelihood prospects. Through a conceptual, rather than empiricist, lens, the study delineates how infrastructural modernization, digital governance, and cultural economy initiatives in Srinagar engender ripple effects upon peripheral agrarian landscapes, artisanal production clusters, and marginalized rural habitations. The analysis foregrounds dimensions such as agricultural market integration, tele-health accessibility, skill dissemination, eco-tourism linkages, and e-governance diffusion, while simultaneously acknowledging the unevenness, fragility, and contradictions inherent in these processes. By extrapolating illustrative examples from across the Valley, the research underscores that the smartness of Srinagar cannot be meaningfully appraised in isolation, but only in relation to the degree of inclusivity and sustainability it bequeaths upon its rural hinterland. The paper ultimately argues that Srinagar’s transformation, if imbued with participatory governance, ecological prudence, and socio-cultural sensitivity, holds the potential to evolve from a narrowly urban project into a regionally integrative paradigm of smart development. Conversely, if construed merely as an infrastructural or technological spectacle, it risks reinforcing spatial and socio-economic asymmetries. Thus, the Srinagar Smart City initiative emerges simultaneously as a developmental opportunity and a conceptual crucible, where the very meaning of “smartness” in peripheral contexts is subject to redefinition.